2012
DOI: 10.1111/j.1360-0443.2012.03928.x
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Δ9‐tetrahydrocannabinol (dronabinol) impairs on‐the‐road driving performance of occasional and heavy cannabis users but is not detected in Standard Field Sobriety Tests

Abstract: Dronabinol (medicinal tetrahydrocannabinol) impairs driving performance in occasional and heavy users in a dose-dependent way, but to a lesser degree in heavy users due possibly to tolerance. The Standard Field Sobriety Test is not sensitive to clinically relevant driving impairment caused by oral tetrahydrocannabinol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 24 publications
11
81
0
Order By: Relevance
“…Similar arguments can be made for other difficult tasks performed by humans during a typical day. Others have reported substantial tolerance to the effects of THC on simulated driving tasks or other psychomotor tasks, which would seem consistent with our results (Bosker et al, 2012; Downey et al, 2013; Schwope et al, 2012). In these studies, blood levels of THC or its metabolites were not determined across groups with known patterns of prior THC exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Similar arguments can be made for other difficult tasks performed by humans during a typical day. Others have reported substantial tolerance to the effects of THC on simulated driving tasks or other psychomotor tasks, which would seem consistent with our results (Bosker et al, 2012; Downey et al, 2013; Schwope et al, 2012). In these studies, blood levels of THC or its metabolites were not determined across groups with known patterns of prior THC exposure.…”
Section: Discussionsupporting
confidence: 93%
“…To some degree, it is probable that the population of impaired drivers shows some "baseline impairment", compared to healthy volunteers, as quite a large proportion of subjects is impaired also at very low drug concentrations. This situation, which is also indicated in previous studies (Bosker et al 2012;D'Souza et al 2008), could be caused by changes in brain function and behavior, which could be caused by drug use, but is not related to the acute intoxication (Bosker et al 2013). If this was true, an increase in traffic risk is expected in this population, also when very low blood drug levels are present.…”
Section: Discussionsupporting
confidence: 62%
“…Future studies are needed to determine whether these changes revert back to normal following protracted abstinence from marijuana use. Existing literature shows that cognitive alterations and CB1 receptor down-regulation in regular marijuana users may return to normal values due to neuroadaptive phenomena occurring after periods of abstinence (51)(52)(53). Although our study cannot address whether the structural alterations observed are permanent or reversible, such an investigation would provide important information as to the trajectory of these effects.…”
Section: Discussionmentioning
confidence: 88%